Does uterus volume affect the total laparoscopic hysterectomy outcomes? : Results of total laparoscopic hysterectomy - Adiguzel, Cevdet; Destegül, Emre; Acar Şirinoğlu, Hicran; Uysal, Gülsüm (Journal of Surgery and Medicine, 2022)
Background/Aim: Increased uterus weight, high body mass index (BMI), and history of abdominal surgeries increase the risk of complications in total laparoscopic hysterectomy (TLH), similar to other types of surgery. However, there are conflicting reports about improving technology. This study aimed to retrospectively investigate the clinical features and postoperative results of TLH cases regarding uterine volume performed for benign reasons in our clinic. Methods: In this retrospective cohort study, 252 patients were included. The demographic data of all patients, including BMI, pre-operative uterine volumes, operation times, number of cesarean sections, history of lower abdominal operation, indications, pre-operative and postoperative hemoglobin differences, complications, length of hospital stay, and final pathologies were reviewed. The uterine volume was measured using the prolate ellipsoid formula before surgery, using the maximum length and anteroposterior and transverse diameters of the uterine corpus. The normal uterine volume with these measurements (8 cm long, 4 cm high, and 5 cm wide) was estimated as 83.2 cm3. The patients were classified into two groups according to uterine volume (normal volume ≤ 83.2 or above). Surgical outcomes of patients were compared between groups. Results: Two-hundred-fifty-two women were included in the study. The mean uterine volumes of groups 1 and 2 were 53.66 cm3 (2.25) and 296.33 cm3 (6.25), respectively. In group 1, the mean operation time was 111.14 (6) min, compared to 118.2 (3.06) min in group 2; there was no significant difference (P = 0.164). The mean postoperative hospital stays of groups 1 and 2 were 3.21 (0.15) and 3.34 (0.09) days, respectively, and there was no significant difference (P = 0.706). The mean blood loss values of groups 1 and 2 were 1.34 g/dl (0.19) and 1.16 g/dl 0.06), respectively. Conclusion: According to our results, TLH is a safe method even in patients with a larger uterus; operating time, blood loss, and postoperative hospital stays did not differ according to uterine volume.